BENTUK DAN FUNGSI SATIRE DALAM AKUN YOUTUBE TEKOTOK - Rahmawatim, Solikhah Anita; Sanubarianto, Salimulloh Tegar; Mulyani, Wahyu (Kantor Bahasa Provinsi Maluku, 2024)
Abstract Language is a communication tool that humans use to communicate to convey their intentions and meanings to achieve their respective goals according to the wishes of the speaker and the interlocutor. Cloaking the meaning of speech is then called satirical language. The Tekotok YouTube account presents many short videos in the form of animations containing comedy, knowledge, anxiety, satire, criticism and personal experiences in their work. This research uses descriptive research. This research describes the satirical language style found in videos uploaded by the Tekotok YouTube account. The method used is a qualitative approach. This data collection technique is gradual, namely, listening, observing, collecting video screenshot data, and evaluating the use of satirical language styles in videos uploaded to the Tekotok YouTube account. Then the results of these observations are classified based on the style of satirical language used. Data was collected with 6 video titles, including “Nabung Dosa Calon Pemimpin”, “Hones Translator Koruptor”, “500 T”, “Sifat Pemimpin Negeri Kotok”, and “Korupsi”. In this video, 8 dialogues were found containing satirical language, consisting of 2 dialogues using Horatian satire, 2 dialogues using Juvenalian satire, and 4 dialogues using Mennipean satire. Keywords: Satire Language Style, YouTube, Video, Tekotok. Abstrak Bahasa adalah alat komunikasi yang digunakan manusia untuk berkomunikasi. Akun YouTube Tekotok menyajikan video singkat yang di dalamnya menggunakan gaya bahasa satire. Penelitian ini memiliki tujuan, yaitu mendeskripsikan bentuk-bentuk bahasa satire dan mendeskripsikan fungsi-fungsi bahasa satire dalam akun Youtube Tekotok. Penelitian ini menggunakan penelitian secara deskriptif. Metode yang dilakukan adalah pendekatan kualitatif. Teknik pengumpulan data ini bertahap, yakni menyimak, mengamati, mengumpulkan data tangkapan layar video, serta mendeskripsikan bentuk dan fungsi gaya bahasa satire dalam akun Youtube Tekotok. Terkumpul data dengan delapan judul video, yaitu Nabung Dosa Calon Pemimpin, Hones Translator Koruptor, 500 T, Nyari Suara, 44 Miliar, Sifat Pemimpin Negeri Kotok, Kelakuan Rakyat Negeri Kotok, dan Korupsi. Dalam video ini ditemukan 15 dialog mengandung bahasa satire yang terdiri atas 5 dialog menggunakan gaya bahasa satire horatian, 4 dialog menggunakan gaya bahasa satire juvenalian, dan 6 dialog menggunakan gaya bahasa satire mennipean. Kata kunci: gaya bahasa satire, YouTube, video, Tekotok